2011
DOI: 10.1007/s13131-011-0112-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and physiological parameters of the second generation selected and control groups of Pinctada martensii

Abstract: In May of 2007, the second generation selected (SS) and control (SC) groups of pearl oyster Pinctada martensii were established by selecting 10% breeders with the largest and mean shell length, respectively, from the first generation selected group. Growth performance of the SS and SC groups were compared on the basis of measurement data at Days 8, 18, 60, 95, 195 and 365. On Day 365, 100 individuals (60.0-75.0 mm at shell length) were sampled from each group and then subjected to the experiment where physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…P. f. martensii is the primary species cultured for marine pearls in China and Japan (Wang et al, 2011a). The pearl oyster industry has become one of the most important mariculture industries in several southern provinces of China, including Guangdong, Guangxi, and Hainan (Wang et al, 2004;Deng et al, 2009aDeng et al, , 2011He et al, 2021;Xu et al, 2021). However, the conditions are changing due to the slow growth and mass mortalities of oysters (Deng et al, 2011;Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…P. f. martensii is the primary species cultured for marine pearls in China and Japan (Wang et al, 2011a). The pearl oyster industry has become one of the most important mariculture industries in several southern provinces of China, including Guangdong, Guangxi, and Hainan (Wang et al, 2004;Deng et al, 2009aDeng et al, , 2011He et al, 2021;Xu et al, 2021). However, the conditions are changing due to the slow growth and mass mortalities of oysters (Deng et al, 2011;Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The selected group displayed a 15.2% genetic gain in adult SL relative to the control after two generations of selection for superior growth in the base population of pearl oyster. There were significant correlations among the four growth traits (SH, SL, SW, and TW) (Deng et al ). Results demonstrated that the pearl diameter, weight, and nacre thickness showed significantly positive correlations with SH, SW, and TW (Shi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, improvement of growth traits for recipient oysters can improve the pearl quality (Inoue et al 2011). To improve the productivity of P. 1 Correspondence to: aimwang@163.com fucata martensii, selective breeding programs have been initiated since 2002 and have led to the improvement of cultured stocks (Deng et al 2011).…”
mentioning
confidence: 99%
“…penguin , a swift growth in the full diagonal length, shell height and hinge length with a declined growth were found from juvenile stage to adult stage (Gu et al, ). Genetic gains were also reduced for shell height and length at larval stages than the juvenile and adult growth period (Deng, Yu, Du, Wang, & Fu, ). In pearl oyster Pi.…”
Section: Growth Regulatorsmentioning
confidence: 99%
“… Ref. (Deng, Fu, Liang, Du, & Xie, ; Deng, Yu, et al, ; Doroudi et al, ; Joubert et al, ; Liang et al, ; Mondal, ; Taylor et al, ). …”
Section: Growth Regulatorsunclassified